Legislative Efforts at Curbing Tax Avoidance and Tax Evasion in Nigeria: A Legal Infraction - Ierkwagh, Kwaghkehe; Shima, Vitalis Akase (ABUAD Private and Business Law Journal, 2018)
Tax is a potentially powerful instrument for raising government revenue to meet government expenditure in both developed and developing economies, Nigeria is not an exception. However, tax resistance which manifest in form of tax avoidance and evasion constitutes a major impediment to revenue generation in Nigeria. Legislative enactments have therefore been put in place in the country to curb the menance. As palatable as these enactments may appear, this paper has found that they represent a major infraction on the rights of Nigerians. The right to fair hearing, right to own property and right to privacy have been completely eroded in the legislative attempts at curbing the menance of tax resistance. In order to balance the need for the preservation of human rights in Nigeria, on one hand, and the need for efficient revenue generation, on the other, the paper has advocated the enactment of a Tax Payers’ Bill of Rights to address some of the identified abuses. It is further advocated that section 104(2), (3) and (4) of the Personal Income Tax Act and section 44(2)(a) of the Constitution of the Federal Republic of Nigeria which have completely abrogated the rights to own property and fair hearing of Nigerian Tax Payers be repealed in order to give meaning to the rights as granted under the Constitution.